2014
DOI: 10.1039/c4ra06268j
|View full text |Cite
|
Sign up to set email alerts
|

Structure–color mechanism of iridescent cellulose nanocrystal films

Abstract: Chirality, hydrogen bond interaction and surface charge repulsion among sulfate CNCs have vital impact on the formation of a cholesteric mesogen in a suspension or solidified film. Therefore, changing surface charge density through mechanical disintegration is an effect way to tune the chiroptical properties of iridescent CNC films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
60
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 34 publications
5
60
0
Order By: Relevance
“…According to the literature, we also found that the cholesteric order is conserved for micrometer‐scale distances, much larger than the nanometric length of the CNC rods. The lateral size of the domains was found to be dependent upon many factors, which include the initial film precursor solutions' characteristics as well as the films' production conditions . The cross‐section hetero­geneities are in agreement with the literature: not only the existence of cholesteric planar layers with different pitches but also the micrometer gaps in between .…”
supporting
confidence: 85%
See 1 more Smart Citation
“…According to the literature, we also found that the cholesteric order is conserved for micrometer‐scale distances, much larger than the nanometric length of the CNC rods. The lateral size of the domains was found to be dependent upon many factors, which include the initial film precursor solutions' characteristics as well as the films' production conditions . The cross‐section hetero­geneities are in agreement with the literature: not only the existence of cholesteric planar layers with different pitches but also the micrometer gaps in between .…”
supporting
confidence: 85%
“…The optical properties of the films were found to depend upon the characteristics of the colloidal suspensions, which pass through different stages upon solvent evaporation and before the formation of the film. In order to use these films for optical applications, many attempts have been undertaken to control their optical properties and mainly their reflection characteristics . If casting followed by a slow solvent‐evaporation method is used, the resulting films show iridescent colors and its cross‐sections can present several domains with different pitch values.…”
mentioning
confidence: 99%
“…We also tuned the ultrasonic time and temperature to reduce the FWHM of included‐angle, as shown in Figures and , respectively. The aim is to study the potential effect of ultrasonic time and temperature on the dispersion state of SCNC in water . The FWHM of included angle then decreased to be as small as 6.73° at 35 °C and 25 min, as shown in Figure d and its inset.…”
Section: Resultsmentioning
confidence: 99%
“…The aim is to study the potential effect of ultrasonic time and temperature on the dispersion state of SCNC in water. [27] The FWHM of included angle then decreased to be as small as 6.73° at 35 °C and 25 min, as shown in Figure 1d and its inset. When the ultrasonic time was too long, the CNC broke, leading to a change in the size of CNC (as shown in Figure S2 in the Supporting Information) and further a less regular arrangement of CNC.…”
Section: Introductionmentioning
confidence: 81%
“…Because of the structure, the films behave as 1D photonic crystals, reflecting circularly polarized light having the same sense as the cholesteric screw orientation . This property of CNCs is attractive for producing iridescent films with many potential applications …”
Section: Methodsmentioning
confidence: 99%